Multimodal Approach of Improving Spatial Abilities - Tamás Balla; Róbert Tóth; Marianna Zichar; Miklós Hoffmann (Multimodal Technologies and Interaction)
Spatial abilities, which are sources of our capacity to understand visual and spatial relations among objects, as well as the abilities to generate, retain, retrieve, and transform well-structured visual information are important in several scientific fields and workplaces. Various tests have already been prepared to measure these abilities, including the Mental Cutting Test, which is considered the golden standard of measurement. However, much less attention is paid to how to prepare students for this test, as well as how to develop these skills most effectively. The purpose of this research is to study the multimodal approach of improving these skills and its effectiveness, i.e., the mixed use of 2D tools similar to the paper-based test, and 3D tools, including augmented reality and web-based interfaces in training students for those kinds of tasks. We want to demonstrate and prove with tests that multimodal modes of training can significantly affect the effectiveness of developing these skills. Moreover, through appropriately combining these methods, they can reinforce each other to form a multimodal approach, which is the most effective way for developing spatial skills and improving students’ performance related to the Mental Cutting Test.